The Role of Employer Branding in Employee Retention: A Bibliometric Perspective - Nurhasanah, Intan; Qolby, Aufa Abiyya (Banking & Management Review, 2025)
Introduction/Main Objectives: Employer branding is a vital strategy in human resource management, addressing both talent attraction and retention. While its role in recruitment is well-documented, its impact on employee retention is underexplored, especially in the context of technological advancements and workforce diversity. Background Problems: Organizations face challenges in retaining employees due to evolving workforce expectations, hybrid work models, and increased competition for talent. How employer branding can mitigate turnover and foster loyalty remains a critical question for modern organizations. Novelty: This study integrates bibliometric analysis with practical insights, highlighting emerging trends such as hybrid work, diversity, and technology integration. It identifies research gaps in sector-specific branding strategies and the unique needs of gig economy workers and millennials, providing a more comprehensive understanding. Research Methods: A bibliometric analysis of 372 articles published from 2000 to 2024 was conducted using VOSviewer software. Data were categorized into themes such as employee engagement, job satisfaction, and digital transformation. Finding/Results: Employer branding improves employee retention by fostering engagement, promoting a positive work culture, and leveraging technology. Emerging themes like inclusivity and hybrid work reflect modern workforce needs, while gaps remain in sector-specific strategies. Conclusion: Strong employer branding reduces turnover and enhances competitiveness. Organizations must adopt holistic strategies aligning values with employee needs, fostering inclusivity, and utilizing technology. Future research should explore sector-specific and technology-driven branding strategies.